PERAN ASSOCIATION OF SOUTH EAST ASIAN NATIONS (ASEAN) DALAM PENYELESAIAN PELANGGARAN HAK ASASI MANUSIA DI MYANMAR (KASUS AUNG SAN SUU KYI) - , Ida Ayu Diana Wahyudewi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aim of this research was to explore the ASEAN role in the settlement of the violation of human rights in Myanmar, particularly related to the Aung San Suu Kyi case. This research described and analyzed steps that ASEAN should take related to Myanmar human right problems. This research applied the normative research method to analyze the ASEAN role in this matter, paying special attention the Aung San Suu Kyi case by doing research on international regulations, articles and related documents. The data of this research was collected by a study of the relevant literature. The result of this research showed that the Myanmar election of 2010, and the subsequent release of Aung San Suu Kyi from house arrest resulted from the suppression of the international community. On the Myanmar problems of human rights violations, ASEAN revealed its role using a constructive engagement policy in which ASEAN member states were being proactive towards Myanmar without violating the sovereignty of state principles. Despite the fact that ASEAN had established ASEAN Intergovernmental Commision on Human Rights, this commission had failed to show its role in the violation of human rights in Myanmar. Therefore ASEAN should be firmer towards the implementation of human rights as stated in the Charter.